Comparison of Immunohistochemistry and Direct Sanger Sequencing for Detection of the Mutation in Thyroid Neoplasm - Hye-Seon Oh (Endocrinology and Metabolism, 2018)
BackgroundThe BRAFV600E mutation is the most common genetic alteration identified in papillary thyroid carcinoma (PTC). Because of its costs effectiveness and sensitivity, direct Sanger sequencing has several limitations. The aim of this study was to evaluate the efficiency of immunohistochemistry (IHC) as an alternative method to detect the BRAFV600E mutation in preoperative and postoperative tissue samples.MethodsWe evaluated 71 patients who underwent thyroid surgery with the result of direct sequencing of the BRAFV600E mutation. IHC staining of the BRAFV600E mutation was performed in 49 preoperative and 23 postoperative thyroid specimens.ResultsSixty-two patients (87.3%) had PTC, and of these, BRAFV600E was confirmed by direct sequencing in 57 patients (91.9%). In 23 postoperative tissue samples, the BRAFV600E mutation was detected in 16 samples (70%) by direct sequencing and 18 samples (78%) by IHC. In 24 fine needle aspiration (FNA) samples, BRAFV600E was detected in 18 samples (75%) by direct sequencing and 16 samples (67%) by IHC. In 25 core needle biopsy (CNB) samples, the BRAFV600E mutation was detected in 15 samples (60%) by direct sequencing and 16 samples (64%) by IHC. The sensitivity and specificity of IHC for detecting the BRAFV600E mutation were 77.8% and 66.7% in FNA samples and 99.3% and 80.0% in CNB samples.ConclusionIHC could be an alternative method to direct Sanger sequencing for BRAFV600E mutation detection both in postoperative and preoperative samples. However, application of IHC to detect the BRAFV600E mutation in FNA samples is of limited value compared with direct sequencing.